Possibilities of Builiding The Social Security of Precariat: Polish Experinces And Challenges - Michał CZUBA (Communications of International Proceedings, 2022)
The precariat is a new social category that exists in all countries around the world and consists of people who work in the gig economy and/or are employed under civil law contracts. One of the key factors that determines membership of the precariat is the uncertainty felt by individuals in the labour market as a result of, inter alia, being employed on flexible forms. The research aim of this article is to define the specificity of the Polish precariat and their sense of social security in the context of the current employment support and social policy of the Polish government. The utilitarian goal is to evaluate the “Polish Deal” programme currently presented by the Polish government in terms of its strengths and weaknesses in order to reduce the precariat phenomenon and boost the Polish precariat’s sense of social security. The article also attempts to demonstrate the effects of actions taken by the Polish government since 2015, which were aimed at improving the situation on the precariat labour market.
Keywords: social security; precariat; politics; employment; unemployment.